VD_FINDINFO HC / 2011 / 657 vom 7. November 2011 - VD Tribunal cantonal (2011)
DÉFAUT CACHÉ, GARANTIE EN RAISON DES DÉFAUTS DE LA CHOSE | 197 al. 1 CO, 197 al. 2 CO, 199 CO, 201 al. 1 CO, 201 al. 3 CO